Finite p-groups all of whose maximal subgroups, except one, have its derived subgroup of order ≤ p - Janko, Zvonimir (Glasnik matematički, 2012)
Let G be a finite p-group which has exactly one maximal subgroup H such that |H'|>p. Then we have d(G)=2, p=2, H' is a four-group, G' is abelian of order 8 and type (4,2), G is of class 3 and the structure of G is completely determined.
DOI funktioniert nicht
Gesehen am 23.02.2018